Investing in Human Capital in Difficult Times: Maine’s Competitive Skills Scholarship Program - Butler, Sandra; Deprez, Luisa; Dorrer, John; Main, Auta (Maine Policy Review, 2010)
The authors describe how the Competitive Skills Scholarship Program, administered by the Maine Department of Labor, aims both to meet the needs of Maine employers through improved access to a skilled labor force and to improve job prospects for low-income Mainers by providing access to education, training, and support. They note that many currently unemployed workers do not have the skills or experience to take advantage of the new job opportunities that are likely to arise, and that there is a demonstrated correlation between higher levels of education and training and both higher income and reduced unemployment. Preliminary data suggest a high level of satisfaction by program participants and that graduates are finding positions in high-growth, high-wage occupations.
Keywords: Maine; scholarship programs; worker training programs